On the Study of Agape and its Role in Social Community’s Rebuilding: Compare with the Concept Eros - ZHANG, Yong-Chao (Journal of Research for Christianity in China (JRCC), 2025)
As we know, the Christian is famous for the dogma of love as a global religion. Love come from the concept Agape, which is a special word for display the meaning of God’s love. Because of the origin of Agape is God, therefore, we know that agape is active and selfless. God love people with no conditions, because God is infinite. Gradually, human beings show the meaning of love God and love neighbors with the word agape. Even though, agape is different from the word Eros which has no relationship with God. Moreover, we would found the concept agape play an important role in the rebuilding of modern social community.
Keywords: Agape; Eros; Community